2010
DOI: 10.1111/j.1601-183x.2010.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors of reaction time performance: DRD4 7-repeat allele associated with slower responses

Abstract: Twin studies indicate substantial inherited components in cognitive abilities. One of the most extensively studied candidate genes of cognitive functioning is the dopamine D4 receptor gene (DRD4), which has been suggested to be related to attentional disorders. Based on reaction time data of 245 Caucasians participating in different cognitive tasks, slower responses characterized the group with the 7-repeat allele. This effect was present in both sexes and was not because of fatigue. To our knowledge, this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 48 publications
4
31
1
5
Order By: Relevance
“…Increase in net photosynthetic rate may convert light energy more efficiently in photochemical reactions under the combined treatment of EDTA and Cu 2+ which resulted in increased growth and biomass (Table 1). This increase in photosynthetic pigments with EDTA under Cu stress does not coincide with the report of Székely et al (2011). They reported that a decrease in photosynthetic pigments may be due to oxidative stress generated by EDTA.…”
Section: Edta Mitigates the Cu Toxicity In B Napuscontrasting
confidence: 62%
See 2 more Smart Citations
“…Increase in net photosynthetic rate may convert light energy more efficiently in photochemical reactions under the combined treatment of EDTA and Cu 2+ which resulted in increased growth and biomass (Table 1). This increase in photosynthetic pigments with EDTA under Cu stress does not coincide with the report of Székely et al (2011). They reported that a decrease in photosynthetic pigments may be due to oxidative stress generated by EDTA.…”
Section: Edta Mitigates the Cu Toxicity In B Napuscontrasting
confidence: 62%
“…Similar results have been reported in sweet sorghum and CAT (e, f), APX (g, h), and soluble protein (i, j) in roots and leaves of B. napus seedlings grown in solution culture with increasing Cu concentrations (0, 50, and 100 μM) treated without and with 2.5 mM EDTA. Different letters indicate that values are significant different at P<0.05 sudangrass seedlings with EDTA application under Cu stress (Székely et al 2011). In this study, the increase in Cu translocation from root to shoot might be due to chelating effects of EDTA (Gunawardena et al 2010).…”
Section: Edta Mitigates the Cu Toxicity In B Napusmentioning
confidence: 94%
See 1 more Smart Citation
“…Like other polymorphisms findings, some of the initial results regarding DRD4 polymorphism with less statistical power cannot be replicated (Kluger et al, 2002). A recent study showed a robust association between the 7-repeat allele and a slow processing speed (Szekely et al, 2011). Another interesting recent finding was the association between the 7-repeat risk allele and decreased performance of the creativity measured by a divergent thinking test in an Israeli sample (Mayseless et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Previous genetic studies have shown the effects of the 7-repeat allele in several behavioral variables (Szekely et al, 2011) and regional gray matter structures (Durston et al, 2005;Monuteaux et al, 2008;Shaw et al, 2007). In particular, using a large sample size, Shaw et al (2007) have shown that the 7-repeat allele carriers have a thinner right orbitofrontal/inferior prefrontal and posterior parietal cortex.…”
Section: Introductionmentioning
confidence: 98%